2010
DOI: 10.4049/jimmunol.0902153
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in the Central Nervous System and Th17 Responses Are Inhibited by IFN-γ–Induced IL-18 Binding Protein

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 47 publications
(54 reference statements)
0
32
1
1
Order By: Relevance
“…However, our data shown in Fig 6, as well as that reported by others (15,17), suggest that IL-18 or IL-18R may also have a key role in promoting IL-17 production and autoimmunity. One explanation for this is that IL-18 may function at least in part through induction of IL-1.…”
Section: Il-18 With Il-23 Promotes Il-17 Production By Cd4 T Cells contrasting
confidence: 40%
See 2 more Smart Citations
“…However, our data shown in Fig 6, as well as that reported by others (15,17), suggest that IL-18 or IL-18R may also have a key role in promoting IL-17 production and autoimmunity. One explanation for this is that IL-18 may function at least in part through induction of IL-1.…”
Section: Il-18 With Il-23 Promotes Il-17 Production By Cd4 T Cells contrasting
confidence: 40%
“…It has also been shown that overexpression of IL-18bp, an endogenous inhibitor of IL-18, reduced Th17 responses and the severity of EAE in mice, independently of IFN-g (15). Furthermore, it was demonstrated that IL-18-deficient mice are unable to mount autoreactive Th1 responses and are resistant to the development of EAE (16).…”
Section: Foxp3mentioning
confidence: 93%
See 1 more Smart Citation
“…While detection of live B. burgdorferi microorganisms in patients is difficult, chronic Lyme disease displays clinical similarities with autoimmune disorders such as rheumatoid arthritis (RA) and multiple sclerosis (MS), in which T cells are known to play important roles. Pathogenic Th17 cells (CD4 ϩ T cells) play a prominent role in the pathogenesis of these diseases (8,21,23).…”
Section: Interleukin-23 (Il-mentioning
confidence: 99%
“…It was first described as interferon-␥ (IFN-␥)-inducing factor, because of its ability to induce IFN-␥ production from T cells in synergy with IL-12 (37) and as such is an important promoter of Th1-type immune responses and an enhancer of T cell cytotoxicity (16,57). Additionally IL-18 has a role in Th2 (8)-and Th17-driven processes (30,44).…”
mentioning
confidence: 99%